2017
DOI: 10.3389/fpls.2017.01428
|View full text |Cite
|
Sign up to set email alerts
|

Seed Carotenoid and Tocochromanol Composition of Wild Fabaceae Species Is Shaped by Phylogeny and Ecological Factors

Abstract: Carotenoids distribution and function in seeds have been very scarcely studied, notwithstanding their pivotal roles in plants that include photosynthesis and phytohormone synthesis, pigmentation, membrane stabilization and antioxidant activity. Their relationship with tocochromanols, whose critical role in maintaining seed viability has already been evidenced, and with chlorophylls, whose retention in mature seed is thought to have negative effects on storability, remain also unexplored. Here, we aimed at eluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 70 publications
1
25
0
1
Order By: Relevance
“…Although β‐carotene and its isomers were identified as major compounds across the samples, carotenes were found in lower levels than xanthophylls. Earlier studies found that the photosynthetic tissues of lupin and aromatic herbs provide mainly xanthophylls, with lutein being the most predominant carotenoid . Results from the present investigation support the hypothesis of Mellado‐Ortega and Hornero‐Mendez, who speculated extensively on the reason why lutein is the dominant carotenoid in many botanical species, such as legumes and cereals .…”
Section: Resultssupporting
confidence: 90%
“…Although β‐carotene and its isomers were identified as major compounds across the samples, carotenes were found in lower levels than xanthophylls. Earlier studies found that the photosynthetic tissues of lupin and aromatic herbs provide mainly xanthophylls, with lutein being the most predominant carotenoid . Results from the present investigation support the hypothesis of Mellado‐Ortega and Hornero‐Mendez, who speculated extensively on the reason why lutein is the dominant carotenoid in many botanical species, such as legumes and cereals .…”
Section: Resultssupporting
confidence: 90%
“…The photoprotective role of α-tocopherol is well documented (Munné-Bosch and Alegre, 2002) and is very common in photosynthetic tissues. The other isoforms β and δ are quite rare in most plant species, and γ-tocopherol is more common in seeds (Grusak and DellaPenna, 1999; Fernández-Marín et al 2017). Abbasi et al (2007) found that tobacco seeds increased the amounts of α-tocopherol as DT was acquired during maturation.…”
Section: Discussionmentioning
confidence: 99%
“…The key principles at the core of gene bank operations are the preservation of germplasm identity, maintenance of viability and genetic integrity, and the promotion of access (FAO 2014). In our study, the germplasm quality was analysed in terms of: (1) availability of key data in SBD for taxonomy (plant name), geography (bio-geographic region, country, geo-coordinates and altitude), habitat and population (number of plants found, and sampled and area sampled); (2) current status of plant identification (verified or unverified); and (3) seed quality, quantity and viability.…”
Section: Germplasm Qualitymentioning
confidence: 99%